THE EFFECTIVENESS OF UTILIZING SOCIAL NETWORKS IN SOCIAL INTERACTION REGARDING THE DEVELOPMENT OF THE COVID-19 PANDEMIC AMONG STUDENTS OF IMAM ABDUL RAHMAN BIN FAISAL UNIVERSITY IN DAMMAM - Abdulaziz Ali Alsalman (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Nowadays, civilized nations are concerned with the human energy of their children more than anything else or any other energy, because a person can control what is around him and transform it to be beneficial for his nation and society if he well-prepared a proper preparation that would achieve an integrated growth of his aspects of personality. The stage of university education is considered the most important form of educational stages. The mission through which it is possible to reveal the psychological, mental and cognitive abilities of students and to take care of their growth and direct them in the right direction, and comes through university orientations. The world witnessed tremendous developments in the fields of various sciences, and these developments have led to growth and continuity as there is no known stop in various aspects of life, and among the doors that these developments have touched is the door to the revolution of communication technology, so that the world has become a small village with the facilitation of these communication developments, and methods of transmitting information between different countries.This, of course, affected various sectors of social life, and despite the new era of this culture, it was able to impose its presence in the life of all humanity, as it attracted millions of people with tremendous speed, but in many cases, it became a way of life. It is "the Internet" and for example social networks.